Human Transbodies to HCV NS3/4A Protease Inhibit Viral Replication and Restore Host Innate Immunity - Jittavisutthikul, Surasak; Seesuay, Watee; Thanongsaksrikul, Jeeraphong; Thueng-in, Kanyarat; Srimanote, Potjanee; Werner, Rolf G.; Chaicumpa, Wanpen (Frontiers in Immunology, 2016)
A safe and effective direct acting anti-hepatitis C virus (HCV) agent is still needed. In this study, human single-chain variable fragments of antibody (scFvs) that bound to HCV NS3/4A protein were produced by phage display technology. The engineered scFvs were linked to nonaarginines (R9) for making them cell penetrable. HCV RNA transfected-Huh7 cells treated with the transbodies produced from four different transformed E. coli clones had reduced HCV RNA inside the cells and in the cell spent media, as well as fewer HCV foci in the cell monolayer compared to the transfected cells in culture medium alone. The transbodies treated-transfected cells also had up-expression of the genes coding for the host innate immune response including TRIF, TRAF3, IRF3, IL-28B, and IFN-beta. Computerized homology modeling and intermolecular docking predicted that the effective transbodies interacted with several critical residues of the NS3/4A protease including those that form catalytic triads, oxyanion loop, and S1 and S6 pockets, as well as a zinc binding site. Although insight into molecular mechanisms of the transbodies need further laboratory investigation, it can be deduced from the current data that the transbodies blocked the HCV NS3/4A protease activities leading to the HCV replication inhibition and restoration of the virally suppressed host innate immunity. The engineered antibodies should be tested further for treatment of HCV infection either alone, in combination with current therapeutics, or in a mixture with their cognates specific to other HCV proteins.